263. An Evaluation of Quality Indicators for the Management of Staphylococcus aureus Bacteremia: A Nested Case-Control Study. (31st December 2020) - Simms, Andrew; Schweizer, Marin L; Ohl, Michael; Perencevich, Eli N; Goto, Michihiko
Abstract: Background: Community-acquired Staphylococcus aureus bacteremia (CA SAB) is a common infection with high mortality. Ten Oever et al. recently used expert consensus methods to develop a set of 25 quality indicators for SAB care in five domains (i.e., follow up blood cultures, echocardiography, non-antibiotic interventions including source control, antibiotic treatment, and other management aspects). Associations between these quality indicators and patient outcomes have not been evaluated. We assessed associations between proposed quality indicators and all-cause 30-day mortality among patients with CA SAB. Methods: We conducted a nested case-control study within a described national multicenter cohort of patients with SAB in the Veterans Health Administration (VHA). The cohort included 2, 093 patients who were: 1) admitted to acute care hospitals between 1/2012 and 12/2014 for CA SAB (the first positive blood culture before or within 48 hours of admission with no recent healthcare exposure); 2) survived at least 96 hours after the SAB onset. We identified paired cases (who died within 30 days) and controls (who survived an equal time), matched 1:1 for age (+/- 5 years), gender, admission year and month, and methicillin susceptibility of isolates. We reviewed charts to extract information for quality indicators. We estimated associations between quality indicators and mortality using logistic regression, adjusting for patient demographics and comorbidity. Results: 164 patients (82 cases and 82 controls) were included. The median patient age was 68.5 (IQR: 62–80) years, and 74 (45.1%) had methicillin-resistant isolates. All patients received at least one domain of quality indicator (median: 3 [IQR: 2–4]). When analyzed individually, only two domains (follow-up blood cultures: OR 0.27 [95% CI: 0.11–0.68]; source control: OR: 0.13 [0.05–0.31]) were associated with mortality. There was a dose-response relationship in which more domains received was associated with decreased mortality (Figure). Association Between the Number of Satisfied Quality Indicator Domains and All-Cause 30-day Mortality Conclusion: Among patients with CA-SAB, the number of satisfied quality indicator domains was associated with 30-day mortality with a dose-response relationship. This finding supports the relevance of these quality indicators for SAB management. Disclosures: All Authors : No reported disclosures